2020
DOI: 10.1016/j.jshs.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The tortuous path of lactate shuttle discovery: From cinders and boards to the lab and ICU

Abstract: Highlights In the 2019 American College of Sports Medicine Wolffe lecture George Brooks described history Lactate Shuttle development. Lactate is a fuel energy source, the main gluconeogenic precursor, and a signaling molecule with autocrine, paracrine, and endocrine functions. Endurance training develops the capacities to produce, remove and utilize lactate. Lactate is favored as a fuel by working red muscle, heart, liver, and brain. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 186 publications
(309 reference statements)
2
34
0
1
Order By: Relevance
“…Numerous studies over the intervening period have shown that La − is not merely a dead‐end waste product of anaerobic metabolism, but is instead a continuously produced and removed metabolite that circulates among and within essentially all cells of the body (Brooks, 2018). Both the evidence and the concept have been extensively reviewed previously (Gladden, 1996, 2004 a , b , 2008; Brooks, 2000, 2002, 2007, 2009, 2016, 2018, 2020 b ; Brooks & Gladden, 2003), and the reader is referred to those summaries.…”
Section: Rationale and Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies over the intervening period have shown that La − is not merely a dead‐end waste product of anaerobic metabolism, but is instead a continuously produced and removed metabolite that circulates among and within essentially all cells of the body (Brooks, 2018). Both the evidence and the concept have been extensively reviewed previously (Gladden, 1996, 2004 a , b , 2008; Brooks, 2000, 2002, 2007, 2009, 2016, 2018, 2020 b ; Brooks & Gladden, 2003), and the reader is referred to those summaries.…”
Section: Rationale and Outlinementioning
confidence: 99%
“…Originally conceived as a means to shuttle reducing equivalents among cells, tissues and organs, we now know that La − shuttling fulfils three basic functions: (1) La − is a major, sometimes preferred, energy substrate; (2) La − is the primary gluconeogenic precursor; and (3) La − is a signalling molecule (Brooks, 1986(Brooks, , 2018(Brooks, , 2020b. Workers in diverse fields such as brain metabolism, sepsis, cancer and diabetes research, are employing lactate shuttle theory in an effort to better understand normal and disrupted metabolism in different tissue and cell types.…”
Section: The Lactate Shuttle and The 'Anaerobic Threshold'mentioning
confidence: 99%
“…So far as mitochondrial pyruvate transport and oxidation are concerned, it is known that the putative mPC colocalizes with mitochondrial MCT1 in L6 myocytes. In preliminary studies, colocalization analysis of mMCT1 and mPC1 using Imaris software revealed that both MCT1 and mPC are co-localized to the mitochondria (r 2 = 0.8) (Brooks, 2020c). However, because muscle lactate concentration exceeds that of pyruvate by one (10x) to two (200-400x) orders of magnitude in resting and exercising human muscles, respectively (Henderson et al, 2004), lactate oxidation is dominant in vivo.…”
Section: Contributions From Muscle and Exercise Physiology (The Cell-mentioning
confidence: 99%
“…Take for instance conflations of terms "glycolysis" and "fermentation." In mammalian tissues, glycolysis (i.e., conversion of glucose and glycogen to lactate) is very different from aerobic fermentation of sugar to alcohol by yeast, or the production of swamp gases by anaerobic bacteria as occurs in the colon, at wound sites or in rotting Ferguson et al, 2018;Brooks, 2020c). Conflation of the terms perpetuates the myth of lactate poisoning and thus handicaps understanding of basic biology and its translation.…”
Section: Introductionmentioning
confidence: 99%
“…It is a pleasure to provide a commentary on the outstanding review 1 by Dr. George Brooks that discusses both the discovery and importance of the lactate shuttle. Clearly, Professor Brooks is highly qualified to review this important topic.…”
mentioning
confidence: 99%